2011
DOI: 10.1111/j.1747-0803.2010.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival Implications: Hypertrophic Cardiomyopathy in Noonan Syndrome

Abstract: Noonan syndrome-HCM frequently coexists with structural cardiac malformations, whereas nonsyndromic HCM does not; their natural histories may therefore be different. Late survival is significantly worse for Noonan syndrome-HCM than nonsyndromic HCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 31 publications
3
48
0
Order By: Relevance
“…Positive consequences of genetic testing include relief of uncertainty surrounding a diagnosis, more accurate estimation of transmission risk, and identification of asymptomatic at-risk family members. Genetic confirmation may also enable preemptive screening and treatment of complications such as hypertrophic cardiomyopathy in Noonan syndrome 262 and neuropsychiatric disease in 22q11.2 microdeletion syndrome. 263 Potential harms, which have been addressed through legislation in the United States, include difficulty in acquiring insurance, potential job discrimination, and negative self-image, although this is less relevant in patients with diagnosed or manifest CHD.…”
Section: Genetic Counselingmentioning
confidence: 99%
“…Positive consequences of genetic testing include relief of uncertainty surrounding a diagnosis, more accurate estimation of transmission risk, and identification of asymptomatic at-risk family members. Genetic confirmation may also enable preemptive screening and treatment of complications such as hypertrophic cardiomyopathy in Noonan syndrome 262 and neuropsychiatric disease in 22q11.2 microdeletion syndrome. 263 Potential harms, which have been addressed through legislation in the United States, include difficulty in acquiring insurance, potential job discrimination, and negative self-image, although this is less relevant in patients with diagnosed or manifest CHD.…”
Section: Genetic Counselingmentioning
confidence: 99%
“…Patients with NS have been noted to have a suboptimal outcome to percutaneous balloon pulmonary valvuloplasty (PBPV) for valvar pulmonary stenosis (PS) 13. Additionally, NS patients with a diagnosis of hypertrophic cardiomyopathy (HCM) have been historically noted to have a significantly worse survival over non-syndromic HCM for reasons that are not well understood 12 14 15. The aims of our study were to describe the spectrum, management and prognosis of heart disease in NS and to investigate the cohort for genotype-phenotype correlations.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have indicated that up to 20-30% of patients suffer from hypertrophic cardiomyopathy with one third of cases revealing ventricular outflow tract obstruction [2]. Recent evidence further indicates that survival and long term prognosis is worse in Noonan hypertrophic cardiomyopathy sufferers, when compared to non-syndromic hypertrophic cardiomyopathy patients [3].…”
Section: Discussionmentioning
confidence: 99%